Semiotic Analysis of South Park Cartoon Comedy Season I - Ahmad Shadiqi (English Department, Faculty of Humanities, Andalas University, 2014)
This thesis is a semiotic analysis of a popular American cartoon comedy, South Park. Focusing on the first season of its airing, the study elaborates thirteen episodes of the series. The study is aimed to analyze the signs in the show and to describe the codes in which those signs are organized. The method in collecting the data is based on Berger’s concept of important sign and is analyzed with Chandler’s method of semiotic analysis, including the three-part model of codes. The study finds 21 important signs along with their meanings. In analyzing the data, the collected signs are analyzed by giving a brief explanation of the text as proposed by Chandler. Those sign is elaborated within Hjemslev’s order of signification to describe the message and value in two levels of meaning, denotation and connotation. After the main issues in the signs’ messages and values are collected, the analysis of codes is conducted by referring to those main issues. The study results in some sub-codes divided into three main codes. Social codes as the socio-cultural dimension of sign include social critique, human rights, as well as race and ethnic tolerance. Characterization and sarcastic humor are classified as textual codes, the textual medium in delivering messages and values. Social hypocrisy as the interpretative code reveals the general perspective in interpreting sign.Keywords: semiotics, sign, codes, South Park